2022
DOI: 10.3390/electronics11132021
|View full text |Cite
|
Sign up to set email alerts
|

A Survey on CubeSat Missions and Their Antenna Designs

Abstract: CubeSats are a class of miniaturized satellites that have become increasingly popular in academia and among hobbyists due to their short development time and low fabrication cost. Their compact size, lightweight characteristics, and ability to form a swarm enables them to communicate directly with one another to inspire new ideas on space exploration, space-based measurements, and implementation of the latest technology. CubeSat missions require specific antenna designs in order to achieve optimal performance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(20 citation statements)
references
References 116 publications
0
20
0
Order By: Relevance
“…The features of patch antennas have been listed, considered, and noted in previous review articles [16,17,22,31]. Although the gains in patch antennas are relatively high compared to wire antennas, they are limited owing to their structural features and manufacturing technology [32]. In the same review paper [32], statistical data indicated that helical antennas allow for even more gain within the VHF to S-bands compared to patch/planar antennas and can be easily assembled and deployed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The features of patch antennas have been listed, considered, and noted in previous review articles [16,17,22,31]. Although the gains in patch antennas are relatively high compared to wire antennas, they are limited owing to their structural features and manufacturing technology [32]. In the same review paper [32], statistical data indicated that helical antennas allow for even more gain within the VHF to S-bands compared to patch/planar antennas and can be easily assembled and deployed.…”
Section: Introductionmentioning
confidence: 99%
“…Although the gains in patch antennas are relatively high compared to wire antennas, they are limited owing to their structural features and manufacturing technology [32]. In the same review paper [32], statistical data indicated that helical antennas allow for even more gain within the VHF to S-bands compared to patch/planar antennas and can be easily assembled and deployed. In [33], conical log spiral and quadrifilar helix antennas (QHA) were used for the UHF band, as well as a deployment mechanism that includes spiral pantograph and origami models with a Z-fold configuration.…”
Section: Introductionmentioning
confidence: 99%
“…Antenna design is an important component in satellite systems for both the upstream and downstream communications that connect ground stations to satellites. Their size and weight should be in accordance with the CubeSat, and should provide good radiation performance [ 1 ]. In recent time, the requirements for Multi-Input–Multi-Output (MIMO) antennas for CubeSats operating at 437 MHz, i.e., the amateur UHF band, have increased.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the CubeSat has been used as a scientific application in radio bands [8].The antenna is essential in a CubeSat telecommunication subsystem because it establishes the communication link between the ground station and the CubeSat. So, the CubeSat Antenna is developed in different designs to enhance the operating frequency bands and radiation performance [9,10]. It is essential for the RainCube rainfall radar [8], missions in deep space [11], and the Internet of space [12], and it enables us to see the satellite constellation and the Pleiades in space [13].…”
mentioning
confidence: 99%
“…From [9,10,19], challenges and the restrictions of CubeSat platforms have been studied and considered during the design and integration phase of the antenna with the CubeSat after a deep review of the challenges that face the CubeSat antenna design, and the most common challenges and our contribution towards these challenges are as follows:…”
mentioning
confidence: 99%